2020
DOI: 10.1177/0003134820951432
|View full text |Cite
|
Sign up to set email alerts
|

Simple Versus Radical Resection for Duodenal Adenocarcinoma: A Propensity Score Matched Analysis of National Cancer Database

Abstract: Background Duodenal adenocarcinoma treatment consists of either simple or radical surgical resection. Existing evidence suggests similar survival outcomes between the two but is limited by small numbers and single-institution analysis. We aim to compare survival after partial versus radical resection for duodenal adenocarcinoma using the National Cancer Database (NCDB). Methods Using NCDB results from 2004 to 2014, we compared patients with duodenal adenocarcinoma undergoing partial resection (n = 1247) and ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 35 publications
1
23
0
Order By: Relevance
“…In the last decade, the diagnosis of epithelial neoplasia of the duodenum has been increased by endoscopic examination in Japan; therefore, the development of this diagnostic tool is considered to be a reason for increased findings [4] , [5] , [6] , [7] . Regardless, according to finding DC at an earlier stage that can be locally located in the duodenum, radical surgery seems to be more frequent than in previous periods according to reports and our experiences [1] , [2] , [9] , [10] , [11] , [12] , [13] , [14] , [15] . In fact, our present series of nine patients showed that the first curative case was found in 2014; therefore, preliminary evaluation of surgical treatment for DC was examined in this report.…”
Section: Discussionmentioning
confidence: 79%
See 4 more Smart Citations
“…In the last decade, the diagnosis of epithelial neoplasia of the duodenum has been increased by endoscopic examination in Japan; therefore, the development of this diagnostic tool is considered to be a reason for increased findings [4] , [5] , [6] , [7] . Regardless, according to finding DC at an earlier stage that can be locally located in the duodenum, radical surgery seems to be more frequent than in previous periods according to reports and our experiences [1] , [2] , [9] , [10] , [11] , [12] , [13] , [14] , [15] . In fact, our present series of nine patients showed that the first curative case was found in 2014; therefore, preliminary evaluation of surgical treatment for DC was examined in this report.…”
Section: Discussionmentioning
confidence: 79%
“…In a recent Western series, patients with DC undergoing PD and duodenectomy were compared. The overall survival was not significantly different, although patients undergoing PD had higher morbidity [9] , [10] , [13] . However, it depends on the extension of the tumor into the parenchyma of the pancreas [17] , [18] .…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations